Increasing the Growth of Robusta Coffee Seedlings (Coffea anephora) Through Application of KNO3 and Shallot Extract - Ali, Fandyka Yufriza; Rosdiana, Eva; Rohman, Hanif Fatur; Kusumaningtyas, Rizky Nirmala (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Coffee is one of the plantation commodities that has an important role for the national economy. The dominance of smallholder plantations has made the seedling process one of the keys to the success of coffee cultivation in Indonesia. Optimal seedling growth can be obtained through a good seedling system. One of the efforts to increase the growth seedlings of robusta coffee is by giving shallot extract as a Growth Regulator because it contains auxin. In addition, the addition of KNO3 can optimize nutrient provision. This study aims to determine the response of robusta coffee seedlings due to the application of onion extract and potassium nitrate fertilizer (KNO3). The research was carried out in February – May 2024 at the Jember State Polytechnic Wire House using a Random Group Design Factorial (RGDF) consisting of 2 factors, the first factor was the provision of KNO3 concentration with 3 levels of P0 treatment: 0%; P1: 0.5%; and P2: 1% and the second factor, namely shallot extract with 3 levels of treatment, including; B0: 0%; B1: 50%; and B2: 75%. The results of the study showed that there was an interaction between KNO3 and the addition of shallot extract and affected the growth of Robusta coffee seedlings on the parameters are height, stem diameter, root length, wet weight and dry weight of robusta coffee seedlings. The treatment of KNO3 0.5% and 75% shallot extract (P1B2) gave the best results in Robusta coffee seedlings